(untitled) (KULT_online, 2018)
The volume Metamorphosen von Kultur und Geschlecht, edited by Andreas Langenohl and Anna Schober, focuses on performances of gender in politics, science, fine arts, and popular culture. Through several recent examples, it shows how gender differences are publicly problematized as well as celebrated within social, political, and artistic-aesthetic contexts and how these processes changed in the 20th and 21th centuries. Drawing from studies on genealogies, practices, and the imagining of gender, different processes of meaning production are observed in their entanglement and critically discussed in the context of categorical demarcations. The various cross-disciplinary methods and objects of analysis make the reading of this volume particularly rewarding and highlight the intersections between discourses on the theory of science and political as well as aesthetic practices of gender.